1981
DOI: 10.1056/nejm198102263040902
|View full text |Cite
|
Sign up to set email alerts
|

A Progressive Neurologic Syndrome in Children with Chronic Liver Disease

Abstract: A progressive neurologic syndrome developed in six children with longstanding cholestatic liver disease. The neurologic abnormalities included areflexia, gait disturbance, decreased proprioceptive and vibratory sensation, and paresis of gaze. Serum vitamin E concentrations were uniformly low. Neuropathological studies carried out in two of the three fatal cases revealed degeneration of the posterior column, selective loss of large-caliber, myelinated axons in peripheral nerve, and spheroids in the gracile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(56 citation statements)
references
References 24 publications
4
52
0
Order By: Relevance
“…This is in line with the observed neuropathological changes found in vitamin E-deficient rats [5,44] , monkeys [4] and man [45,46] which are characterized by a primary axonopathy with secondary demyelination. Previous studies have revealed that vitamin E deficiency leads to enhanced oxidative stress in the cerebral cortex as shown by increased concentrations of malondialdehyde [47] .…”
Section: Relationship Between Gene Expression and Neural Abnormalitiesupporting
confidence: 90%
“…This is in line with the observed neuropathological changes found in vitamin E-deficient rats [5,44] , monkeys [4] and man [45,46] which are characterized by a primary axonopathy with secondary demyelination. Previous studies have revealed that vitamin E deficiency leads to enhanced oxidative stress in the cerebral cortex as shown by increased concentrations of malondialdehyde [47] .…”
Section: Relationship Between Gene Expression and Neural Abnormalitiesupporting
confidence: 90%
“…Recently a progressive neurological syndrome in children with chronic liver disease has been documented by Rosenblum et al (1981). The neurological syndrome is very similar to that of our case.…”
Section: Descussionsupporting
confidence: 88%
“…In the present case the serum vitamin E value was extremely low. In the view of the report by Rosenblum et al (1981) such a low serum level of vitamin E may play a role in the pathogenesis of neurological disorders.…”
Section: Descussionmentioning
confidence: 95%
“…We discuss the relationship of these findings to vitamin E replacement in children with chronic cholestasis. vitamin E ; cholestasis ; muscle pathology ; ultrastructureThe relationship between prolonged vitamin E deficiency and neurologic complications in patients with cholestasis has been well documented (Rosenblum et al 1981;Guggenheim et al 1982a Guggenheim et al , b, 1983Alvarez et al 1983;Neville et al …”
mentioning
confidence: 99%